Academic Libraries and the Development Agenda: Librarying the First Aspiration of Agenda 2063 in Ghana - Alua Mary Ann; Danquah Monica Mensah (Open Information Science)
This study sought to assess the contribution of academic libraries in Ghana towards the attainment of Agenda 2063. The study was guided by a survey research design that used a quantitative approach. Questionnaires were used as the main data-collection instrument. Data were collected from 101 library professionals from six university libraries in Ghana. Key findings from the study were that although librarians in Ghana had a fair idea about the sustainable development goals, their knowledge of and awareness of Agenda 2063 in general, and the first aspiration in particular, was still at an infancy level. Indeed, the findings disclosed the involvement of librarians and libraries in various activities that unconsciously contributed towards attaining the seven (7) goals of the first aspiration of Agenda 2063, even though they disagreed that their libraries contributed towards attaining some of the goals of this aspiration. Recommendations based on the study findings were directed towards the need for management of academic libraries to make a conscious effort towards creating awareness and ensuring that activities mapped out, as well as success stories, are shared with society and other stakeholders to be more visible and actively included in decision-making on achieving the development agenda.